Balance of Threat: Finland’s Responds to Potential Threat from Russia Post Russo-Ukrainian Conflict Escalation - Karman, Lalu Ladeva Alfusa'idu; Wiswayana, Wishnu Mahendra (Jurnal Studi Diplomasi dan Keamanan, 2025)
Two abrupt geopolitical events happen between 2022 and 2023. Russia’s invasion of Ukraine in February 2022 and Finland’s application for NATO membership later that year shocked the geopolitical situation in Europe. The potential threat Russia brought upon its closest neighbour, Finland, has resulted in the Balancing action by Finland. Finnish Paradox, the development of Russia’s military, and Moscow’s passive-aggressive history are a few factors that led to Finland’s response to Russia’s potential threat. Balance of Threat theory will be used to explain the potential threat to Finland from Russia and how it shapes Finland’s geopolitical decision. The research will surround the question of “How does Finland respond to the potential threat from Russia Post Russo-Ukrainian Conflict Escalation?” and the hypotheses of “Finland joins NATO in 2023 because it is taking a balancing action towards Russia due to the potential threat Russia poses against Finland”. Thus, this research will scrutinize why and how Finland responded to the Moscow-Kiev conflict escalation. Russia’s numerous options of military strength added to its past aggressive behaviour, total aggregate and offensive power, and proximity to Finland, are adequate to be considered a threat to Finland. Therefore, Finland’s balancing action towards Russia’s potential threat is valid.